The Neuroendocrine System as a Model to Evaluate Experimental Gene Therapy - Herenu, Claudia B.; Brown, Oscar A.; Sosa, Yolanda E.; Morel, Gustavo R.; Reggiani, Paula C.; Bellini, Maria J.; Goya, Rodolfo G. (Current Gene Therapy, 2006)
The implementation of experimental gene therapy in animal models of neurological diseases is an area of growing interest. Although the neuroendocrine system offers unique advantages for the assessment of in vivo gene therapy, little work has been done in this model. Here we review the core of documented studies in which in vivo gene therapy has been implemented in the neuroendocrine system of rodent models. In the hypothalamus, restorative gene therapy has been successfully implemented in Brattleboro rats, an arginine vasopressin (AVP) mutant which suffers from diabetes insipidus, in Koletsky (faκ/faκ) and in Zucker (fa/fa) rats which have leptin receptor mutations that render them obese, hyperphagic and hyperinsulinemic. In the above models, viral vectors expressing AVP, leptin receptor b and proopiomelanocortin, respectively were stereotaxically injected in the relevant hypothalamic regions. In rats, aging brings about a progressive degeneration and loss of hypothalamic tuberoinfundibular dopaminergic neurons, which are involved in the tonic inhibitory control of prolactin secretion and lactotrophic cell proliferation. Stereotaxic injection of an adenoviral vector expressing Insulin-like Growth Factor-I (IGF-I) was able to correct their chronic hyperprolactinemia and restore tuberoinfundibular dopaminergic (TIDA) neuron numbers. In young and old F-344 male rats, Glial Cell Line-derived Neurotrophic Factor (GDNF) gene delivery in the hypothalamus induced body weight loss. These results suggest that further implementation of gene therapy strategies in neuroendocrine models may be highly rewarding.
Keywords: Brattleboro